Enhancing Assessment Efficiency And Quality: Design And Implementation Of A Mobile-Assisted Evaluation System For English Language Teachers - Abdurashidova Mohinur O‘tkir qizi; Xaitova Odina Xushnud qizi; Ergashev Usmon Elbek o‘g‘li (Genius Journals, 2025)
The rapid advancement of mobile technologies has created unprecedented opportunities for transforming educational practices, particularly in language teaching and assessment. This study explores the development of a mobile application designed to assist English language teachers in the assessment process, addressing critical challenges in efficiency, consistency, and feedback quality. Through a comprehensive analysis of current assessment practices, technological frameworks, and pedagogical requirements, this research presents a systematic approach to mobile application development that integrates artificial intelligence, user-centered design principles, and evidence-based assessment methodologies. The findings demonstrate that mobile-assisted assessment tools can significantly reduce teachers' workload while maintaining or improving assessment quality, providing timely feedback to learners, and generating valuable analytics for instructional decision-making. This article contributes to the growing body of knowledge on educational technology by offering practical insights into the design, development, and implementation of mobile assessment solutions in language education contexts.
Keywords: mobile learning; assessment automation; English language teaching; educational technology